(3bjGS eDTQGJ XGgQI GdabQ aj GdhWf GdYQHjs - (3OGhO eMeO YOfGf(B, (3GdYPGQjs; (3gOi RhjQ eNda GdOYej(B, s ((3YeGf(B:s (3OGQ LQjQ(B,s, 2010)
(3fXQI aj eaGgje GdabQ hfXQjGJg, XGgQI GdabQ aj GdhWf GdYQHj, GdJMdjd Gdcej GdGbJUGOjs
(3GdeQGLY HGdYQHjI hGdCLfHjI U(B.183 (3dedGMb U(B.199s
Keywords: (3GdabQs; (3GdabQ (B-(3GdhWf GdYQHjs